2013
DOI: 10.1091/mbc.e13-04-0204
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase CK2 phosphorylates and activates p21-activated kinase 1

Abstract: P21-activated kinase 1 (PAK1) activation is achieved through relief of autoinhibition. The authors show that this event is not sufficient to bring about PAK1 activation but is required for CK2-dependent PAK1S223 phosphorylation, which enables PAK1 to be catalytically competent. S223 phosphorylation is crucial for PAK1 GTPase-dependent and GTPase-independent activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 48 publications
6
26
0
Order By: Relevance
“…Our results have demonstrated that CK2 phosphorylation of Ser-223 is crucial for activation of PAK1 (26), and that this process is regulated by PI3K (this study). The kinase activity of a constitutively active PAK1 (PAK1 H83,86L ), postulated to mimicGTPase-inducedstructuralchanges(47),requiresphosphorylation of Ser-223, suggesting that Ser-223 may become available for phosphorylation by CK2 after the conformational change (26). Therefore, PI3K-dependent, CKIP-1-mediated recruitment of CK2␣ to the plasma membrane is essentially required for the activation of PAK1.…”
Section: Pi3k Regulation Of Pak1supporting
confidence: 71%
See 4 more Smart Citations
“…Our results have demonstrated that CK2 phosphorylation of Ser-223 is crucial for activation of PAK1 (26), and that this process is regulated by PI3K (this study). The kinase activity of a constitutively active PAK1 (PAK1 H83,86L ), postulated to mimicGTPase-inducedstructuralchanges(47),requiresphosphorylation of Ser-223, suggesting that Ser-223 may become available for phosphorylation by CK2 after the conformational change (26). Therefore, PI3K-dependent, CKIP-1-mediated recruitment of CK2␣ to the plasma membrane is essentially required for the activation of PAK1.…”
Section: Pi3k Regulation Of Pak1supporting
confidence: 71%
“…We have recently demonstrated that CK2 catalyzes phosphorylation of PAK1 at Ser-223, which is critical for the activation of the kinase (26). Here, we show evidence that CKIP-1 appears to recruit CK2␣ to PAK1 in response to EGF in a PI3K-dependent manner.…”
supporting
confidence: 53%
See 3 more Smart Citations